Intervening to strengthen sovereignty: The lessons of the UN Intervention Brigade for global peacekeeping. (June 2016) - Piiparinen, Touko
The main significance and novelty of the Intervention Brigade established by the United Nations (UN) Security Council in March 2013 in the Democratic Republic of the Congo have previously been attributed to its robust mandate, enhanced capacities and offensive concept of operations. At the tactical, strategic and doctrinal levels of analysis, the Brigade could be considered a continuum of the robust and technological turn of UN peacekeeping, which has continued for more than a decade and is reinvigorated in the so-called new generation of peacekeeping tactics outlined in the New Horizon document. However, this article argues that the most profound significance and novelty of the Brigade reside at the underlying paradigmatic level, which has been ignored in the previous literature. The Brigade embodies not only robust capacities and mandate (peacekeeping with muscles) but also a new peacekeeping paradigm, namely, sovereignty-building (peacekeeping for body politic). The sovereignty-building paradigm is aimed at creating or strengthening the positive and negative sovereignty of the host government. The Brigade reinforces the positive sovereignty of the Congolese government by boosting its self-directive domestic and foreign policy, political will, ownership and responsibility vis-à-vis its regional peers, for example, by making its exit strategy conditional on the Congolese own Rapid Reaction Force. With regard to negative sovereignty, the Brigade contributes to the reinstatement of territorial integrity and supreme state authority by neutralising militia groups.